Glucose patterns during the OGTT and risk of future diabetes in an urban Indian population: The CARRS study. (April 2017) - Hulman, Adam; Gujral, Unjali P.; Narayan, K.M. Venkat; Pradeepa, Rajendra; Mohan, Deepa; Anjana, Ranjit Mohan; Mohan, Viswanathan; Færch, Kristine; Witte, Daniel R.
Highlights: Latent class analysis identifies distinct OGTT glucose patterns among Asian Indians. A high 30-min glucose peak was associated with increased risk of diabetes. High proportion of those with a elevated 30-min glucose and T2DM at follow-up were NGT at baseline. Internal time points during the OGTT add clinically useful information to traditional measures. Abstract: Aims: Traditionally, fasting and 2-hour post challenge plasma glucose have been used to diagnose diabetes. However, evidence indicates that clinically relevant pathophysiological information can be obtained by adding intermediate time-points to a standard oral glucose tolerance test (OGTT). Methods: We studied a population-based sample of 3666 Asian Indians without diabetes from the CARRS-Chennai Study, India. Participants underwent a three-point (fasting, 30-min, and 2-h) OGTT at baseline. Patterns of glycemic response during OGTT were identified using latent class mixed-effects models. After a median follow-up of two years, participants had a second OGTT. Logistic regression adjusted for diabetes risk factors was used to compare risk of incident diabetes among participants in different latent classes. Results: We identified four latent classes with different glucose patterns (Classes 1–4). Glucose values for Classes 1, 2, and 4 ranked consistently at all three time-points, but at gradually higher levels. However, Class 3 represented a distinct pattern, characterized by high 30-min (30 minPG), normal fasting (FPG) and 2-h (2hPG) plasma glucose, moderately high insulin sensitivity, and low acute insulin response. Approximately 22% of participants were categorized as Class 3, and had a 10-fold risk of diabetes compared to the group with the most favorable glucose response, despite 92.5% of Class 3 participants having normal glucose tolerance (NGT) at baseline. Conclusions: Elevated 30 minPG is associated with high risk of incident diabetes, even in individuals classified as NGT by a traditional OGTT. Assessing 30 minPG may identify a subgroup of high-risk individuals who remained unidentified by traditional measures.